2017
DOI: 10.1021/acsnano.7b07200
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Structured Illumination Expansion Microscopy Reveals Microbial Cytoskeleton Organization

Abstract: Recently developed tissue-hydrogel methods for specimen expansion now enable researchers to perform super-resolution microscopy with ~65 nm lateral resolution using ordinary microscopes, standard fluorescent probes, and inexpensive reagents. Here we use the combination of specimen expansion and the optical super-resolution microscopy technique structured illumination microscopy (SIM) to extend the spatial resolution to ~30 nm. We apply this hybrid method, which we call ExSIM, to study the cytoskeleton of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 50 publications
1
122
0
Order By: Relevance
“…X10 thus provides a toolset for cheap (< 2$ for all reagents used in one experiment, except antibodies) multi-color super-resolution imaging, which can be performed on widely available epifluorescence setups. This procedure provides a resolution that is superior to current combinations of conventional expansion microscopy and super-resolution, as published very recently using structured illumination [31], since this resulted in a resolution of~30 nm, lower than A B C Figure 3. The resolution of X10 is~25 nm.…”
Section: Resultsmentioning
confidence: 95%
“…X10 thus provides a toolset for cheap (< 2$ for all reagents used in one experiment, except antibodies) multi-color super-resolution imaging, which can be performed on widely available epifluorescence setups. This procedure provides a resolution that is superior to current combinations of conventional expansion microscopy and super-resolution, as published very recently using structured illumination [31], since this resulted in a resolution of~30 nm, lower than A B C Figure 3. The resolution of X10 is~25 nm.…”
Section: Resultsmentioning
confidence: 95%
“…In principle, super‐resolution instruments can be used with ExM samples to harness the advantages of both methods. Structured illumination microscopy (SIM), for example, was applied to expanded samples to achieve resolutions comparable with those of SMLM, whereas STED combined with ExM (ExSTED) produced a resolution of 10 nm . However, ExSTED cannot utilize the highest STED resolution because photobleaching prevents the use of the maximum depletion intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Will it be possible to achieve an even higher resolution by imaging an expanded specimen with super‐resolution microscopes? Until today, two studies have demonstrated such super super‐resolution imaging, one with photoactivated localization microscopy (Tillberg et al ., ) and the other one with SIM (Halpern et al ., ). In both the studies, super‐resolution microscopes were used to image a 4.5‐fold expanded biological specimens and a resolution higher than 60‐nm was achieved.…”
Section: Large‐volume Tissue Imaging Via Exmmentioning
confidence: 97%
“…(E-H) Reproduced with permission from (Ku et al, 2016);Copyright 2016, Nature Publishing Group. ] with photoactivated localization microscopy (Tillberg et al, 2016) and the other one with SIM (Halpern et al, 2017). In both the studies, super-resolution microscopes were used to image a 4.5-fold expanded biological specimens and a res-olution higher than 60-nm was achieved.…”
Section: Large-volume Tissue Imaging Via Exmmentioning
confidence: 99%
See 1 more Smart Citation